A novel EDA1 missense mutation in X-linked hypohidrotic ectodermal dysplasia. Issue 11 (March 2020) - Wang, Xu; Zhang, Zhiyu; Yuan, Shuo; Ren, Jiabao; Qu, Hong; Zhang, Guozhong; Chen, Wenjing; Zheng, Shushen; Meng, Lingqiang; Bai, Jiuping; Du, Qingqing; Yang, Dongru; et al.
Abstract : Abstract: A mutation in the epithelial morphogen gene ectodysplasin-A1 ( EDA1 ) is responsible for the disorder X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common form of ectodermal dysplasia. XLHED is characterized by impaired development of hair, eccrine sweat glands, and teeth. This study aimed to identify potentially pathogenic mutations in four Chinese XLHED families. Genomic DNA was extracted from the peripheral blood and sequenced. Sanger sequencing was used to carry out mutational analysis of the EDA1 gene, and the three-dimensional structure of the novel mutant residues in the EDA trimer was determined. Transcriptional activity of NF-κB was tested by Dual luciferin assay. We identified a novel EDA1 mutation (c.1046C>T) and detected 3 other previously-reported mutations (c.146T>A; c.457C>T; c.467G>A). Our findings demonstrated that novel mutation c.1046C>T (p.A349 V) resulted in XLHED. The novel mutation could cause volume repulsion in the protein due to enlargement of the amino acid side chain. Dual luciferase assay revealed that transcriptional NF-κB activation induced by XLHED EDA1 protein was significantly reduced compared with wild-type EDA1. These results extend the spectrum of EDA1 mutations in XLHED patients and suggest a functional role of the novel mutation in XLHED.